PENGARUH DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA KANTOR BPK RI PERWAKILAN PROVINSI BALI - Ni Luh Gede Ranti Andari; I Nengah Aristana (Universitas Triatma Mulya, 2021)
This research is motivated by the phenomenon of employee morale that occurs in government agencies BPK RI Representatives of Bali Province. Spirit of work is seen from several factors including; employee work discipline and employee job satisfaction. Every employee in an agency is required to have high work discipline so that employees can provide good service to the community. Job satisfaction or employee dissatisfaction depends on the difference between what is expected. This study aims to analyze and prove the effect of work discipline and job satisfaction on employee morale. This study uses a descriptive method with a quantitative approach. The sample used in this study amounted to 95 employees at the BPK RI Representatives of the Province of Bali. Multiple linear regression analysis using SPSS software version 23. The regression equation obtained: Y = 15.356+ 0.422X1 + 0.209X2 + ɛ. The results of this study indicate that; First, work discipline has a positive and significant effect on employee morale at the BPK RI Representative Office of Bali Province. Second, job satisfaction has a positive and significant effect on employee morale at the BPK RI Representative Office of Bali Province. Third, work discipline has a more dominant influence on employee morale at the BPK RI Representative Office for the Province of Bali and finally work discipline and job satisfaction have an effect of 21.0% on employee morale at the BPK RI Representative Office of Bali Province. Some suggestions that can be conveyed in this research include; give rewards to employees who have a high discipline attitude and punishment for employees who have a low level of discipline, give full support to increase employee job satisfaction in order to support employee morale.